A Comparison of the Color Stability of Conventional and CAD/CAM Polymethyl Methacrylate Denture Base Materials - Dayan, Cagatay (Acta Stomatol Croat, 2019)
OBJECTIVE: The aim of this study was to evaluate the color stability of a heat polymerized resin, an auto-polymerizing resin, a urethane dimethacrylate resin and a CAD/CAM PMMA block resin stored in different storage media. MATERIALS AND METHODS: 60 disc-shaped specimens (15×2 mm) were fabricated for each group. A total of 240 disc-shaped specimens were thermal-cycled for 5,000 cycles. Then specimens were randomized into 4 groups (n= 15) according to storage media: coffee, coke, red wine and distilled water (control group). The color measurement of each sample was performed using a spectrophotometer before and after storage (after 7 and 30 days), and color changes (ΔE) were calculated. RESULTS: All the denture base materials demonstrated dissimilar color changes after stored in the different storage media in both evaluation stages. In all storage media, CAD-CAM denture base resins showed the minimum in color change. In all denture base resins, red wine showed a higher degree of color change than coke or coffee. CONCLUSION: The color stability of CAD-CAM denture base resins is better than any of the other kind of denture base resins. The color change values of all groups except Eclypse stored in red wine had clinically detectable values.